FILE SHARING SERVER MENGGUNAKAN SAMBA SERVER DAN LINUX UBUNTU 12.04 SERVER - Andi Nugroho; Yopi Handrianto (LPPM Universitas Bina Sarana Informatika, 2016)
Data storage on server laboratory at the computer science when needed.It was because application that progressively and document required was handled by more than one person.Currently there are 6 class space the laboratory contained 30 units of computer in each room. All the time, Laboran (person who manage and work in a laboratory) have to bring harddrive external if you want to install application needed for each the lab, but during this laboran has only two external hard drive. This condition resulted in the process of installation application in the laboratory require a long time. In addition, every month laboran have to make recapitulation contract for 22 person laboratory’s assistant. Now, to make contract assistant in the lab, laboran have to open one of the workstations that is in the fasilkom’s laboratory. This can slow performance, because laboran have to coming into the fasilkom’s laboratory. By the presence of the problems mentioned above, then built a file sharing that is used to hold the application of which is required in the entire room of Fasilkom’s laboratory. In addition, a file sharing this can be used to speed up the emoluments of the preparation of reports on the whole lab assistant that until now had been stored luminance space laboratory so that laboran no need to use more external hard disk in installation perform the process of application by opening the Samba through Windows Server Explorer. It is also the case to compile the report honorarium of the lab’s assistant, laboran enough to use of a file sharing fastly. A file sharing development is using the Linux Ubuntu operating system Version 12.04 and the application of the Samba Servers the Samba to connect storage a file that is in linux so that it can be opened in a windows or linux operating system based. Keywords : File Sharing Server, Samba Server, Linux Ubuntu, Computer Lab.